2020
DOI: 10.1007/s43450-020-00040-6
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Activity of Plectranthus amboinicus Extracts and HPLC Quantification of Rosmarinic Acid

Abstract: Overexposure to sunlight has harmful effects on the skin and can cause erythema and skin cancer. Photoprotective agents are important for preventing exposure to sunlight and are present in the composition of sunscreens. Globally, the use of filters based on natural products has gained interest in scientific studies; in addition to their sunscreen properties, these products demonstrate antioxidant, healing, and moisturizing activity. These favor adequate sun protection due to the wide spectrum of activities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…According to a previous study by Terto et al [ 40 ] and unpublished data [ 41 ], it was seen that RA was the most produced compound in CEE of aerial parts of M. villosa and P. amboinicus , and so because of this, its variation was also evaluated. Thus, it was observed that P. amboinicus had the highest concentrations of this metabolite in a good part of the year and the only month that there was no statistical difference in RA content between the two species was August, when they showed statistically equal production, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to a previous study by Terto et al [ 40 ] and unpublished data [ 41 ], it was seen that RA was the most produced compound in CEE of aerial parts of M. villosa and P. amboinicus , and so because of this, its variation was also evaluated. Thus, it was observed that P. amboinicus had the highest concentrations of this metabolite in a good part of the year and the only month that there was no statistical difference in RA content between the two species was August, when they showed statistically equal production, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…For extract samples of P. amboinicus , a diluent solution used was MeOH:acidified water (0.1% of formic acid) 1:1, the run starts at 50% of solvent B and reaches 60% in 20 min, returning to 50% in 21 min and remaining at this concentration until the end, at 26 min. In this case, the flow rate used was 0.6 mL/min [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant activity of the selected plants was comparable to plants from the same genus. For example, S. articular and S. exilis have inhibited nitric oxide accumulation in cell cultures at 125 μg/ml [ 33 ], methanolic extracts of P. febrifugum exhibited antioxidant activity at 0.02 mg/ml [ 14 ] whereas P. amboinicus has shown promising antioxidant activity at 112.39 μg/ml [ 39 ].…”
Section: Discussionmentioning
confidence: 99%